Des gregario : hommage à Pino Cerami. - Angenot, Eric; Bex, Florent; Conserva, Marcello; Ellena, Veronique; Fink, Christoph; Geys, Jef; Homer, Sébastien; Mathy, Théo; Mouillé, Thierry; Ollivier, Jean-Paul; Piron, François; Ransonnet, Jean-Pierre; et al. (Loverval : Galerie Jacques Cerami, 2002)
Delecluse, Philibert ; Ellena, Veronique ; Lecouturier, Emilie ; Poncelet, Céline ; Geys, Jef ; Mouillé, Thierry ; Muyle, Johan ; Ransonnet, Jean-Pierre ; Tillier, Thierry ; Jamar, Edmond ; Pellizzari, Paolo ; Verheyden, Jan ; Angenot, Eric ; Lecouturier, Jacky ; Rouyre, Daniel ; Fink, Christoph
Frans
Il gregario : hommage à Pino Cerami, Galerie Jacques Cerami Couillet, Loverval, 15 Novembre 2002
boek